2014
DOI: 10.1080/19475705.2014.984246
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall impacts on traffic safety: rain-related fatal crashes in Texas

Abstract: This study uses fatal crash data and geospatial analysis to examine the temporal and spatial distribution of rain-related fatal crashes in Texas from 1982 to 2011. The data were obtained from the Fatality Analysis Reporting System maintained by the National Highway Traffic Safety Administration. The GetisÀOrd G i à (d i ) statistic was used to identify spatial clustering patterns of rain-related fatal crashes and their correlation with rainfall and compare them to spatial patterns of other crashes. The spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A previous study conducted for the nearby city of Riyadh also indicated that on average non-intersection crashes were more fatal compared to intersection crashes [59]. Similarly, the probability of low crash fatality on a rainy day having a large negative value for coefficient (β = −2.532) also appears conflicting to previous studies [60][61][62]. However, it can be argued from several previous studies that inclement weather may cause a significant reduction in vehicle speed [63][64][65].…”
Section: Crash Severity Modeling Using Logistic Regressionmentioning
confidence: 87%
“…A previous study conducted for the nearby city of Riyadh also indicated that on average non-intersection crashes were more fatal compared to intersection crashes [59]. Similarly, the probability of low crash fatality on a rainy day having a large negative value for coefficient (β = −2.532) also appears conflicting to previous studies [60][61][62]. However, it can be argued from several previous studies that inclement weather may cause a significant reduction in vehicle speed [63][64][65].…”
Section: Crash Severity Modeling Using Logistic Regressionmentioning
confidence: 87%
“…The first employed a simple regression model based on a leastsquares estimate and evaluation of the statistical significance of slopes, based on the t test. The second -nonparametric -approach evaluated the significance of the trend by means of the Mann-Kendall (Kendall, 1975) test and Sen's method for assessment of the magnitude of the trend. In the latter approach, the data need not conform to any particular distribution.…”
Section: Methodsmentioning
confidence: 99%
“…On a wider scale, there exist many papers that address the effects of various weather conditions and floods on vehicle transport and accidents (e.g. Andrey et al, 2003Andrey et al, , 2010Eisenberg and Warner, 2005;Brijs et al, 2008;Diakakis and Deligiannakis, 2013;Jackson and Sharif, 2016;Han and Sharif, 2020a, b). However, studies of weather-related casualties arising out of vehicle accidents are absent for the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…Jackson and Sharif ( 9 ) used fatal crash data and geospatial analysis to examine the temporal and spatial distribution of rain-related fatal crashes in Texas from 1982 to 2011. The data obtained from the Fatality Analysis and Reporting System was used to identify spatial clustering patterns of rain-related fatal crashes and their correlation with rainfall and to compare them with spatial patterns of other crashes.…”
Section: Introductionmentioning
confidence: 99%
“…Note: SPF ¼ safety performance function; SD ¼ standard deviation; ADT ¼average daily traffic; vpd ¼ vehicles per day; na ¼ not applicable.362Transportation Research Record 2674(9) …”
mentioning
confidence: 99%